2004
DOI: 10.1186/1476-072x-3-23
|View full text |Cite
|
Sign up to set email alerts
|

Using GIS technology to identify areas of tuberculosis transmission and incidence

Abstract: Background: Currently in the U.S. it is recommended that tuberculosis screening and treatment programs be targeted at high-risk populations. While a strategy of targeted testing and treatment of persons most likely to develop tuberculosis is attractive, it is uncertain how best to accomplish this goal. In this study we seek to identify geographical areas where on-going tuberculosis transmission is occurring by linking Geographic Information Systems (GIS) technology with molecular surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 28 publications
3
40
1
2
Order By: Relevance
“…The worst affected districts were the Southern, West South West and Eastern districts. Studies describing geographic clustering of TB cases found that the most common risk factors for clustering were low socioeconomic status, homelessness, poor housing and low education attainment [30,31] Successful transmission of TB require the presence of infectious cases that interact with susceptible uninfected individuals for a longer period of time [32] Conditions that affect early TB diagnosis, early treatment and access to social services therefore promote ongoing transmission of TB. West South West and…”
Section: Plos Onementioning
confidence: 99%
“…The worst affected districts were the Southern, West South West and Eastern districts. Studies describing geographic clustering of TB cases found that the most common risk factors for clustering were low socioeconomic status, homelessness, poor housing and low education attainment [30,31] Successful transmission of TB require the presence of infectious cases that interact with susceptible uninfected individuals for a longer period of time [32] Conditions that affect early TB diagnosis, early treatment and access to social services therefore promote ongoing transmission of TB. West South West and…”
Section: Plos Onementioning
confidence: 99%
“…Analysis of the tuberculosis genotype distribution of bacterial isolates provides a method to identify areas of high tuberculosis incidence as well as areas with ongoing transmission of specific bacterial strains. High rates of clustered genotypes in an area suggests that ongoing tuberculosis transmission among patients in that community is likely (Moonan et al 2004). Areas with increased unique isolates suggest that the infections were acquired elsewhere鈥攖hat is, they are imported (Barnes and Cave 2003).…”
mentioning
confidence: 99%
“…En definitiva, la ubicaci贸n pasada de la tuberculosis en una comunidad, hablando desde el punto de vista epidemiol贸gico, puede ser la mejor variable predictiva de la ubicaci贸n de los futuros casos de tuberculosis. Moonan et al aplicaron un principio similar y combinaron el an谩lisis de informaci贸n georreferenciada con la vigilancia epidemiol贸gica molecular para identificar las zonas geogr谩ficas con mayor transmisi贸n de la misma cepa y mayores tasas de infecci贸n (12,13).…”
Section: Discussionunclassified